ISOLASI SENYAWA TRITERPENOID EKSTRAK ETANOL DAUN JERUJU (ACHANTUS ILICIFOLIUS) DAN AKTIVITAS ANTIBAKTERINYA TERHADAP S. AUREUS DAN E. COLI - Latief, M.; Meriyanti, M.; Fadhilah, N.; Tarigan, I. L.; Ayu, A. N.; Maharani, R.; Aulia, E.; Siregar, D. (Jurnal Kimia (Journal of Chemistry); Vol. 16, No.1, Januari 2022DO - 10.24843/JCHEM.2022.v16.i01.p05, 2022)
Staphylococcus aureus and Escherichia coli are pathogenic microbes cause of skin infection and diarrhoea. Infections can be resolved with use of natural antibiotics. Previous research has shown A. ilicifolius has potential as a natural antibiotic because some parts of this plant have antimicrobial actives. This study aimed to isolate the bioactive compound from the ethanol extract of A. ilicifolius leaf and test the antibacterial bioactivity against S. aureus and E. coli . The isolation of the compounds was carried out by Vacuum Liquid Chromatography (VLC) and the antibacterial activity was tested using disc diffusion method. Twelve fractions were obtained from the VLC, where crystals were gained for the fraction 3 (F3). The crystals are recrystallized with n-hexane to obtain F3 isolates. The purity of the isolates was tested by Thin Layer Chromatography (TLC) by using 3 eluents followed by characterization and antibacterial assay. Fourier-Transform Infrared (FTIR) interpretation indicated that F3 isolate was triterpenoid compound having -OH group (3321.96 cm -1 ), -CH aliphatic (2954.95 cm -1 ), -C=C (1661.16 cm -1 ), -CH (1447.93 cm -1 , 1378.11cm -1 ), -CO (1050.54 cm -1 ), -C=C alkenes (881.11 cm -1 ). UV-Vis spectrum showed that the F3 isolate had a maximum wavelength (? max) at 208 nm and 230 nm which indicated the presence of a conjugated C=C group. The results of antibacterial activity test showed that F3 isolate had low antibacterial activity against E. coli and S. aureus . Keywords : antibacterial, E. coli, jeruju (A. ilicifolius), S. aureus, triterpenoid.